An Analysis of a Local and International University-Graduated Teachers Questioning in English for Specific Purposes Class - Irene Rosalina; Slamet Setiawan; Suhartono Suhartono (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Purpose - The study investigated the display and referential questions used by the local and International educated background teacher in English for Specific Purposes (ESP) classroom to promote communicative English class. Design/methodology/approach - The study was qualitatively held, to find out the answer to the research questions, classroom observations, and interviews with two teachers were conducted. Findings - The results indicated that both of the teachers asked higher-order questions in referential type more frequently than teachers in other studies and it could trigger communication effectively. the teachers delivered the questions within their styles. The local educated teacher used mixed Indonesian-Javanese and English to help the students understood the questions and respond well, but the internationally educated teacher employs the questions into whole English. She probes the questions a lot of time to make the questions understandable and simpler. The wait time given was much longer. Some analysis questions were composed to gain the student's braveness to express their answer. Originality/value - This study offered recommendations for effective teachers’ questioning types and techniques for the development of learners’ communicative skills, especially in an ESP class. Paper type – Research paper